Factor completely 10xy + 3y + 20ax + 6a.(10x − 3)(y − 2a)

(10x − 3)(y + 2a)

(10x + 3)(y + 2a)

(10x + 3)(y − 2a)

Answers

Answer 1
Answer:

Answer:

Option 3 is correct.

Step-by-step explanation:

The given expression is

10xy+3y+20ax+6a

This expression can be written as

(10xy+3y)+(20ax+6a)

Take out the common factors from each parenthesis.

y(10x+3)+2a(10x+3)

Now, take out the common factor (10x+3).

(10x+3)(y+2a)

Therefore option 3 is correct.

Answer 2
Answer: 10 xy + 3y + 20 ax + 6a = y(10x+3) + a(20x+6) = y(10x+3)+2a(10x+6)= 
(y+2a)(10x+3)

Related Questions

Write y= -3/4 x-6 in standard form using integers.
(x − 2) is a factor of x4 + 2x3 − 7x2 − 8x + 12.
A full-length mirror cost $144.99 when the CPI was 163. What will a full-length mirror cost when the CPI is 211, to the nearest cent?a) $305.93 b) $214.59 c) $187.68 d) $88.95 If it's not too much to ask, could you thoroughly explain it with exact steps so I can do it myself. Thank you plenty.
Please help I don't know what to do for number 40
Factorise-              6y-15y^2     HELP

If 2x = 5, 3y = 4, and 4z = 3, what is the value of 24xyz ?

Answers

Replacing in the equation;
24xyz
=24 *(5/2)*(4/3)*(3/4)
=24*(60)/(24)
=60

it is 60
because 2x×3y×4z=5×4×3    24xyz=60

Identify the mode in the following set of numbers: 2, 5, 7, 9, 15, 14, 12, 8, 4 ,2.a. 2,
b. 7,
c. 8,
d. 15

Answers

the mode in a set is a number that appears the most. so the answer is a.2

Suppose ∠A and ∠B are complementary angles, m∠A = (3x + 5)°, andm∠B = (2x – 15)°. Solve for x and then find m∠A and m∠B.

Answers

         m∠A + m∠B = 90
(3x + 5) + (2x - 15) = 90
(3x + 2x) + (5 - 15) = 90
                  5x - 10 = 90
                      + 10  + 10
                         5x = 100
                          5      5
                           x = 20

m∠A = 3x + 5
m∠A = 3(20) + 5
m∠A = 60 + 5
m∠A = 65

m∠B = 2x - 15
m∠B = 2(20) - 15
m∠B = 40 - 15
m∠B = 25
m∠A + m∠B = 90

(3x + 5) + (2x - 15) = 90

(3x + 2x) + (5 - 15) = 90

5x - 10 = 90

5x - 10 +10 = 90+10

5x = 100

5x/5 = 100/5      Divide \ both \ sides \ by \ 5

x = 20                 Solutions

m∠A = 3x + 5     (x=20)

m∠A = 3(20) + 5          Substitute \ x \ for \ 20

m∠A = 60 + 5               Simplify

m∠A = 65


m∠B = 2x - 15

m∠B = 2(20) - 15

m∠B = 40 - 15

m∠B = 25

Find the value of t in the equation t+5+3t=1

Answers

t+5+3t=1\nt+3t+5=1\n4t+5=1\n4t+5-5=1-5\n4t=1-5\n4t =-4\n\n\boxed{\bf{t=-1}}
First combine like terms.  1t+3t=4t
5+4t=1
Now subtract 5 from both sides.
4t=-4
Now divide both sides by 4.
t=-1
To check,  let's plug in -1 for t.
-1+5+3*-1=
3*-1=-3
-1+5+-3=1
t=-1

What does square root x^16 equal?

Answers

sqrt(x^16) is x^8.
As you can see, x^8 * x^8 = x*x*x*x*x*x*x*x * x*x*x*x*x*x*x*x which equals x^16
I don't know why Cortesalondra28 deleted my answer to the question and sayid it was wrong..
the square root is of 16 is 4, not 8.

While your statement X*X*X*X*X*X*X*X    *     X*X*X*X*X*X*X*X does equal x^16, that is not what the question is asking. 


Ginny is studying a population of frogs. She determines that the population is decreasing at an average rate of 3% per year. When she began her study, the frog population was estimated at 1,200. Which function represents the frog population after x years?

Answers

Answer:

y = 1200(0.97)^x

Step-by-step explanation:

Ginny determines that the population is decreasing at an average rate of 3% per year.

So, this is an exponential decay case

Formula : y = a(1-r)^n

where a is the amount after n years

a is the initial amount

r is the rate of depreciate

n is the number of years

Now we are given that When she began her study, the frog population was estimated at 1,200.

So, a=1200

r = 3% = 0.03

n =x

Substitute the values in the formula:

y = 1200(1-0.03)^x

y = 1200(0.97)^x

Hence function represents the frog population after x years is y = 1200(0.97)^x

Hello,

x_(0)=1200

x_(1)=(97)/(100)*1200

x_(2)=((97)/(100))^2*1200

x_(3)=((97)/(100))^3*1200
...
x_(n)=((97)/(100))^(n)*1200